Islam or Muslims didn't attack Salman Rushdie, a criminal did - Hasan, Md. Mahmudul (The New Straits Times Press (M) Bhd, 2022)
ssociating Islam with fearful concepts and the one-sided caricaturing of Muslims as mired in fanaticism have now become clichés. However, it is hard to miss the stark contrast between the media treatments of the two similar incidents that happened within a span of less than 24 hours and in the same country (USA). Rightly, the religion of Ricky W. Shiffer and its followers have been kept at bay in the discussions of his actions. But, why is it different in the case of Hadi Matar? Despite the media barrage of negative images of Islam and Muslims, I believe it is not difficult for a sensible person to understand that the writer Salman Rushdie was attacked by a rascal, not by his religion or its followers.